On the Catholic Parish in Kosovska Mitrovica in 1941, Janez Frančišek Gnidovec, and Josip Ujčić and His Appeal for the Salvation of the Serbian People in the Independent State of Croatia - Jovanović, Zoran M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper examines the history of the Catholic parish of St. Michael the Archangel during the first months of the Second World War, when in April 1941 the Kingdom of Yugoslavia was partitioned by Hitler and Mussolini, and their puppets (Bulgarians, Hungarians, and Albanians), while Serbia was placed under a quisling regime. The parish had its liturgical and administrative seat in Kosovska Mitrovica, a town in Kosovo and Metohija (Kosmet), and before the war, its members were predominantly Slovenes and Croats. Among Albanians—who largely practised Islam inherited from the Ottoman period—there were roughly sixty Catholic families. Prior to the war, the parish numbered around 1,500 members, later several hundred fewer, with the majority residing in Kosovska Mitrovica and its immediate surroundings. Until the outbreak of war, it was unusually extensive, encompassing northern Kosovo and reaching as far as Sandžak and eastern Montenegro. This fact is significant, as historians have paid little attention to its existence. Drawing on previously unknown archival materials, this paper also provides an overview of the broader circumstances. Following the so-called April War of 1941, when the Nazi–Fascist coalition occupied Yugoslavia, Kosovo and Metohija were fragmented, which—alongside the suffering of the Serbian population in the region—made the activity of the Catholic Church increasingly difficult. At that time, Croats employed in the mines and mining industry around Kosovska Mitrovica were the first to leave the parish, returning to their homeland without knowing that it would soon be transformed into the newly created Independent State of Croatia. As a consequence of the territorial changes brought about by wartime geostrategic and economic interests, Archbishop Josip Ujčić of Belgrade petitioned the Vatican to transfer those areas of his jurisdiction that had fallen under Bulgarian control to the Ordinariate of the Skopje Diocese. At the same time, he sought approval for the part of Kosovo occupied by the Third Reich to be placed under the jurisdiction of the Ordinariate of the Belgrade Archdiocese—an area that coincided with part of the parish of Kosovska Mitrovica, which, following the arrival of the Nazis, was incorporated into quisling Serbia. Of particular importance is the fact that in his communications with the Vatican Secretariat of State, Archbishop Josip Ujčić emphasized that Serbia was under occupation (“territorio occupato dall’esercito tedesco”). In doing so, he clearly demonstrated loyalty to Yugoslavia and an explicit anti-fascist and anti-Nazi stance. Ujčić thereby distinguished himself from most members of the former Yugoslav Bishops’ Conference, led by the Archbishop Alojzije Stepinac of Zagreb (currently a candidate for canonisation), who from the very first day of the Independent State of Croatia—carved out of Yugoslav territories—glorified this entity, which could not have existed without Hitler’s extensive military and political support. In the international and interconfessional context, it is particularly significant that Archbishop Josip Ujčić simultaneously appealed to the Vatican to prevent genocide against the Serbian people in the Independent State of Croatia. In our conclusion, this very appeal contributed to his later neglect as a multifaceted and positive historical figure—both in the Vatican and within the Catholic Church in Croatia—despite his Croatian origin. By contrast, Alojzije Stepinac was promoted as a hero, although he certainly was not one, as our research has demonstrated. The parish of St. Michael the Archangel was administered by Slovenian Lazarists, that is, members of the Slovenian Province of the Congregation of the Mission of St. Vincent de Paul. This circumstance provides sufficient reason to consider the activity of Bishop Janez Frančišek Gnidovec of Skopje, since it was at his invitation that they came to Kosovo and Metohija. The broader context suggests that he may have sought to restructure the clergy in his diocese, particularly because many Catholic priests of non-Slavic origin had until then shown an inclination toward Greater Albanian policy, that is, Italian imperialism. It is also important to note that in condemning the Kingdom of Yugoslavia—especially the Serbian people and its leaders—these priests employed a linguistic repertoire almost identical to that cultivated by the ideologues of the ultranationalist Ustasha movement, who—within the Croatian people—were crucial to the founding of the Independent State of Croatia. The same or similar formulations were later echoed by the Yugoslav communists as well. Taking all this into account, many of the circumstances surrounding the history of the parish of Kosovska Mitrovica during the Second World War appear to have continued in later periods, which may be one of the reasons why its history was forgotten. In fact, several reasons contributed to this neglect. One of them was the immediate arrest of the parish priest Ivan Strašek, a Slovene, by the Gestapo following the German occupation of Kosovska Mitrovica; he was subsequently transferred to Belgrade. This event would perhaps be less significant were it not for indications that Strašek sympathized with the National Liberation Movement. After the establishment of communist/socialist Yugoslavia, this fact was concealed, as it did not fit the officially constructed past. For the Albanian population, guided by the ideology of Greater Albania, it was equally undesirable, since it contradicted the program of an ethnically homogeneous Kosovo and Metohija. As a result, the Serbian people were subjected to persecution by Albanians throughout the region even at the very beginning of the Second World War.